Women's Decision on Contraceptive Use in Ethiopia: Multinomial Analysis of Evidence From Ethiopian Demographic and Health Survey - Zerihun Kura Edossa; Tilahun Fufa Debela; Biru Abdissa Mizana (SAGE Publishing, 2020)
Background: Women are left out of the conversation on contraceptive use due to a variety of reasons. One of the reasons women have reported for their nonuse of family planning method is that they do not decide to use or not to use it. This study aimed to assess the women's decision-making on contraceptive use and identify its associated factors. Methods: Data for this study were extracted from the national representative 2016 Ethiopian Demographic and Health Survey. Data were collected using 2-stage cluster design, in which enumeration areas forming the first stage and households making the second stage. The analysis was done using multinomial logistic regression using STATA software version 14. Results: The study revealed that one-fourth (24.3%) 95% CI (23.7%-25.1%) decision was made by women. The multinomial analysis demonstrated women's decision-making on contraceptive use was influenced by the age of women 15 to 19 years (adjusted odd ratio [AOR] = 0.327, 95% CI: 0.175-0.613), 20 to 24 years (AOR = 0.510, 95% CI: 0.390-0.666), and 25 to 29 (AOR = 0.557 95% CI: 0.460-0.675); place of residence (urban; AOR = 1.637, 95% CI: 1.331-2.015) and region in which the women dwell and husbands education; occupation of both woman and her husband; and number of children ever born were the factors significantly associated with the outcome variable. Conclusions: Women's decision-making on contraceptive utilization was low. It was influenced by age, place of residence and region, education, occupation, and number of children ever born.